Paris-Princeton Lectures on Mathematical Finance 2013 Editors: Vicky Henderson, Ronnie Sircar - Benth, Fred Espen; Crisan, Dan; Guasoni, Paolo; Manolarakis, Konstantinos; Muhle-Karbe, Johannes; Nee, Colm; Protter, Philip (Lecture Notes in Mathematics, 2013)
The current volume presents four chapters touching on some of the most important and modern areas of research in Mathematical Finance: asset price bubbles (by Philip Protter); energy markets (by Fred Espen Benth); investment under transaction costs (by Paolo Guasoni and Johannes Muhle-Karbe); and numerical methods for solving stochastic equations (by Dan Crisan, K. Manolarakis and C. Nee).The Paris-Princeton Lecture Notes on Mathematical Finance, of which this is the fifth volume, publish cutting-edge research in self-contained, expository articles from renowned specialists. The aim is to produce a series of articles that can serve as an introductory reference source for research in the field.